Specificity of The Pornography Law Over The Electronic Information and Transactions Law on Cyberporn Criminal Acts Via Whatsapp Telecommunication - Utama, Ghenta Werdana; Elda, Edita (Universitas Sultan Ageng Tirtayasa, 2025)
Currently, there are still a lot of and rampant dissemination of pornographic content through social media, especially through whatsapp as happened in decision number 200/Pid.Sus/2022/Pn.Jmb which befell a female victim against the dissemination of the victim's personal video carried out by her own boyfriend which resulted in the victim feeling ashamed of it, there are 2 (two) rules specifically regulating cyberporn crimes, namely the Pornography Law and the ITE Law. The formulation of the problem of this study is How is the proof in the case of the decision Number 200/Pid.Sus/2022/PN.Jmb? Based on the results of the research, there are 2 (two) laws that are specific in regulating the spread of pornography in electronic media or cyberporn, the principle of systematic lex specialist is needed in its application. In the context of dissemination through electronic media, such as in Decision Number 200/Pid.Sus/2022/PN.Jmb, the ITE Law is more relevant to ensnare perpetrators in terms of the use of electronic media in the distribution of content that violates morality. In addition, there is also evidence in the form of 6 (six) sheets of pornographic photo screenshoots and 1 flash disk containing pornographic videos as valid evidence according to Article 5 Paragraph (1) of the ITE Law. Decision Number 200/Pid.Sus/2022/Pn.Jmb the judge used the Pornography Law because it meets the elements of Article 4 Paragraph (1) of the Pornography Law. According to the author, the application of the Pornography Law is not appropriate because dissemination through social media and electronic evidence is more specifically regulated in the ITE.